Pengembangan Model Aplikasi Pembukuan Pada Usaha Laundry - Wahyu Hadikristanto (Jutisi : Jurnal Ilmiah Teknik Informatika dan Sistem Informasi, 2022)
The management of the “Laundry Bagus” business is still managed with a paper recording system, starting from receiving customer orders to purchasing raw materials and management reporting, and has not implemented an accounting-based governance system, resulting in process errors, and slow in the process of retrieval and presentation of data and information. This paper presents a bookkeeping application design that can be used by the management of the Good Laundry Business in managing the activities of the service business being carried out. The application system is designed using structured tools and object-oriented tools, and developed using the Visual Basic.NET programming language and MySQL database. The field observation method is used in studying the running system, as well as the interview method in a series of system requirements elicitation activities. The results of needs elicitation formulate system process requirements and functional requirements in the form of: Customer data collection function, incoming and outgoing laundry, and activity reporting function. The system process model is presented in a flowmap, the functional model is presented in a use case diagram, the system logic model is presented in an activity diagram, and the database model is presented in a database relationship diagram.Keywords: Bookkeeping Application; Laundry Business; Visual Basic.NET; Mysql AbstrakPengelolaan bisnis Laundry Bagus masih dikelola dengan sistem pencatatan di kertas, mulai dari penerimaan pesanan pelanggan hingga pembelian bahan baku dan pelaporan manajemen, serta belum menerapkan sistem tata kelola berbasis akuntansi, sehingga menimbulkan kesalahan proses, serta lambat dalam proses temu kembali serta penyajian data dan informasi. Paper ini menyajikan rancangan aplikasi pembukuan yang dapat digunakan oleh manajemen Usaha Laundry Bagus dalam mengelola aktivitas usaha jasa yang dijalankan. Sistem aplikasi didesain menggunakan tools terstruktur dan tools berorientasi objek, serta dikembangkan menggunakan bahasa pemrograman Visual Basic.NET dan database MySQL. Metode Observasi lapangan digunakan dalam mempelajari sistem yang sedang berjalan, serta metode wawancara dalam rangkaian kegiatan elisitasi kebutuhan sistem. Hasil elisitasi kebutuhan merumuskan kebutuhan proses sistem dan kebutuhan-kebutuhan fungsional berupa: fungsi pendataan Pelanggan, cucian masuk dan cucian keluar, serta fungsi pelaporan kegiatan. Model Proses Sistem disajikan dalam flowmap, model fungsional disajikan dalam Use Case Diagram, model logik sistem disajikan dalam Activity Diagram, serta model database disajikan dalam diagram relasi database.